The value of T1 mapping and intravoxel incoherent motion parameters in predicting PD-L1 expression and dynamically monitoring immunotherapy in advanced lung cancer - Han, Qijia; Li, Shulin; Xiang, Zhiming (Frontiers in Oncology, 2026)
PurposeTo investigate the value of T1 mapping and intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) quantitative parameters in predicting PD-L1 expression and dynamically monitoring immunotherapy efficacy in advanced lung cancer.Materials and methods23 patients pathologically diagnosed with advanced lung cancer were collected. Patients underwent T1 mapping and IVIM examinations pre- and post-immunotherapy. The relationship between PD-L1 expression levels and quantitative parameters was analyzed. The changes of quantitative parameters during treatment were compared between the effective and ineffective groups. The predictive value of quantitative parameters for immunotherapy efficacy was analyzed using area under the curve (AUC).ResultsIn terms of predicting PD-L1 expression, there were no significant differences in the T1, apparent diffusion coefficient (ADC), perfusion fraction (f), true diffusion coefficient (D), and pseudo-diffusion coefficient (D*) values between the positive and negative groups (all p>0.05). After immunotherapy, the effective group showed a lower T1 value (p = 0.008) and a higher ADC value (p = 0.013), with slight increases in f, D, and D* values. The ineffective group had slight increases in T1 and D values, and slight decreases in ADC, f, and D* values. Compared to the ineffective group, the effective group had a lower post-treatment T1 value (p = 0.019) and a higher ΔADC value (p = 0.031). The AUCs of the post-treatment T1 and ΔADC values in predicting immunotherapy efficacy were 0.871 and 0.886, respectively.ConclusionT1 mapping and IVIM quantitative parameters may reflect potential trends in predicting PD-L1 expression, have certain value in monitoring the dynamic changes during immunotherapy in advanced lung cancer, and are expected to provide meaningful imaging biomarkers for individualized immunotherapy decision-making.